2020
DOI: 10.1007/s10915-020-01222-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ROW, ESDIRK, and BDF2 for Unsteady Flows with the High-Order Flux Reconstruction Formulation

Abstract: We conduct a comparative study of the Jacobian-free linearly implicit Rosenbrock-Wanner (ROW) methods, the explicit first stage, singly diagonally implicit Runge-Kutta (ESDIRK) methods, and the second-order backward differentiation formula (BDF2) for the high-order flux reconstruction/correction procedure via reconstruction (FR/CPR) solution of the unsteady Navier-Stokes equations. Pseudo-transient continuation is employed to solve the nonlinear equation at each stage of ESDIRK (excluding the first stage) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…To solve Eq. ( 9), it can be rewritten as @Q @s ¼ RðQ; rQÞ; (10) and the linearly implicit Rosenbrock-Wanner (ROW) Runge-Kutta method 53 was used for time integration. The general formulation of ROW method is written as follows:…”
Section: B Spatial Discretization and Time Integration Methodsmentioning
confidence: 99%
“…To solve Eq. ( 9), it can be rewritten as @Q @s ¼ RðQ; rQÞ; (10) and the linearly implicit Rosenbrock-Wanner (ROW) Runge-Kutta method 53 was used for time integration. The general formulation of ROW method is written as follows:…”
Section: B Spatial Discretization and Time Integration Methodsmentioning
confidence: 99%
“…The Flux Reconstruction/Correction Procedure via Reconstruction (FR/CPR) [20][21][22][23][24][25][26] method is used to solve the governing equations. A brief introduction of the FR/CPR method is discussed in this section for the sake of completeness, but a full discussion of the method can be found in [20].…”
Section: Spatial Discretization and Time Integration Methodsmentioning
confidence: 99%
“…The explicit first stage, singly diagonally implicit Runge-Kutta (ESDIRK) method [25,26] was used for time integration, which is written as…”
Section: Spatial Discretization and Time Integration Methodsmentioning
confidence: 99%
“…As a further simplification, the explicit singly diagonally implicit Runge-Kutta (ES-DIRK) method employs an explicit first step and thus reduces the degree of the nonlinear systems from SDIRK by one. The comparisons from compressible Navier-Stokes equations indicated that the ESDIRK methods are more efficient than the BDF methods [52,53].…”
Section: Integratormentioning
confidence: 99%